Elusive modes of Foxp3 activity in versatile regulatory T cells - He, Minghong; Feng, Yongqiang (Frontiers in Immunology, 2025)
Foxp3-expressing CD4 regulatory T (Treg) cells play a crucial role in suppressing autoimmunity, tolerating food antigens and commensal microbiota, and maintaining tissue integrity. These multifaceted functions are guided by environmental cues through interconnected signaling pathways. Traditionally, Treg fate and function were believed to be statically determined by the forkhead box protein Foxp3 that directly binds to DNA. However, this model has not been rigorously tested in physiological and pathological conditions where Treg cells adapt their function in response to environmental cues, raising questions about the contribution of Foxp3-dependent gene regulation to their versatility. Recent research indicates that Foxp3 primarily functions as a transcriptional cofactor, whose chromatin interaction is influenced by other DNA-binding proteins that respond to cell activation, stimulation, or differentiation. This new perspective offers an opportunity to reevaluate Foxp3’s activity modes in diverse biological contexts. By exploring this paradigm, we aim to unravel the fundamental principles of Treg cell biology.